2019
DOI: 10.1002/cam4.2403
|View full text |Cite
|
Sign up to set email alerts
|

Selenoprotein M stimulates the proliferative and metastatic capacities of renal cell carcinoma through activating the PI3K/AKT/mTOR pathway

Abstract: High‐throughput sequencing methods have facilitated the identification of novel selenoproteins, which exert a vital role in the development and progression of tumor diseases. Recently, Selenoprotein M (SELM) is upregulated in several types of cancer. However, the biological roles of SELM in renal cell carcinoma (RCC) remain unclear. In this paper, quantitative reverse transcription PCR (qRT‐PCR) and Western blot were used to measure relative levels of SELM in a cohort of RCC tissues with matched normal tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Previous studies have proved the several classical signaling mechanisms were involved in promoting ccRCC, such as VHL/HIF1α [40], PI3K/Akt/mTOR [41], HGF/MET [42], MAPK [43], and Wnt/β-Catenin [44], etc. TRPV1 expression was discovered to be negatively correlated with expression of the key proteins in those pathways and positively correlated to cancer inhibiting genes, p53 and VHL.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have proved the several classical signaling mechanisms were involved in promoting ccRCC, such as VHL/HIF1α [40], PI3K/Akt/mTOR [41], HGF/MET [42], MAPK [43], and Wnt/β-Catenin [44], etc. TRPV1 expression was discovered to be negatively correlated with expression of the key proteins in those pathways and positively correlated to cancer inhibiting genes, p53 and VHL.…”
Section: Discussionmentioning
confidence: 99%
“…SelK and SelS were reported to be involved in degradation of misfolded proteins in endoplasmic reticulum [29]. It has been revealed recently that SelM activates the PI3K/Akt/mTOR pathway and mediate expression of matrix metallopeptidases 2 and 9 in renal cell carcinoma [44]. However, the function of some selenoproteins such as SelO, SelI is not elucidated yet [33,34].…”
Section: Selenium Status and Its Biological Importance: Selenium In Tmentioning
confidence: 99%
“…Several additional reports also demonstrated the role of specific selenoproteins in other cancer types. High levels of SELENOM were associated with poor prognosis of renal cell carcinoma (RCC), and preclinical evidence demonstrated that SELENOM silencing was able to block cancer proliferation, invasion, migration, and tumorigenesis, via PI3K/AKt/mTOR pathway inhibition and reduced metalloproteinases (MMP) 2 and 9 expression [13]. SELENOK was found to have a crucial role in the proliferation and activation of immune cells and the promotion of calcium flux that induces melanoma progression [14].…”
Section: Introductionmentioning
confidence: 99%